Ion source and Model 202-G2 Magnetic Electron Multiplier - Bendix Corporation (1958)
Series of photographs depicting an ion source and Model 202-G2 Magnetic Electron Multiplier designed for use with the Bendix Corporation Time-of-Flight Mass Spectrometer. Several of the photographs are annotated with identifications for various component parts, including the dynode and field strips, gate assembly, and glass clamp. One of four component parts of a mass spectrometer, the ion source produces a beam of particles characteristic of the sample material for qualitative and quantitative analysis, while the magnetic electron multiplier is used to detect and amplify ion bunches or peaks. According to notations accompanying the photograph, the Model 202-G2 Multiplier was part of the Rocket-borne and Satellite series.
Keywords: Photoelectric multipliers; Scientific apparatus and instruments; Spectrometer industry; Mass spectrometry; Time-of-flight mass spectrometry; Bendix Corporation; Ion sources; Mass spectrometers